Modernity and changing the 21th century: the history discipline in teaching elementary school II - Aline Gonçalves da Silva; Sônia Aparecida Siquelli (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This partial analysis presented to the qualifying examination is part of the thesis for Master in Education, which is in progress, and is named Teaching practices of History in sixth grade: current challenges. Its purpose is to understand how teachers of History of the sixth grade of Elementary School II, in public schools, in the city of Pouso Alegre - Minas Gerais incorporate the basic contents of the Common Basic Curriculum - CBC. This is the curricular proposal of Minas Gerais State that establishes the methods to be used in the teaching of History and the subjects related to the 6th grade. It is understood as the normative that provides the essential contents to be taught as well as the goals. The hypothesis of this study is that, according to the current context of the 21st Century, dipped in a capitalist worldview, these proposals show a kind of curriculum not experienced in the classroom. For this analysis we´ll use that show the desire of homogeneousness the differences both in cultural and educational levels that, according to Bauman (2001, 2007, 2009, 2010, 2011, 2013), Veiga-Neto (2005, 2008) Veiga-Neto and Saraiva (2009) dismantled at the end of the past century because of the appearance and the changing of values.